Workplace bullying: time to understand its roots - A L Khalib,; H U Ngan, (Department Of Community Health, Faculty of Medicine, Universiti Kebangsaan Malaysia, 2006)
Workplace bullying has drawn greater attention in the last one and half decades. Despite its recognition by many organizations and countries, it is still rife. Why is that so? Could it be that the root of the problem has not been addressed? Or, could it be due to difficulties and resistances in embarking preventive and control measures. In this paper, we will examine the possible causes of workplace bullying based on a proposed model. In depth discussion of the personal and organizational factors are made while the work group and societal factors are dealt with in brief. In summary, the root of workplace bullying is multi-factorial. Understanding the complexity and subtlety of workplace bullying is pertinent in the effort to prevent or curtail it.